Encyclopedia of genocide - Charny, Israel W. (ABC-CLIO, 1999)
Alphabetical entries define names, places, and events associated with genocide, and major sections deal with the Armenian genocide, the Holocaust, and the process, detection, denial, and prevention of genocide.